STATUS KEBERLANJUTAN USAHA PERIKANAN TUNA MADIDIHANG BERBASIS BIOLOGI DAN EKONOMI DI PANGKALAN PENDARATAN IKAN DUFA-DUFA KOTA TERNATE - Kaidati, Bahar; Umsohy, Jehan Safira; Karman, Amirul; Muksin, Darmiyati; Taeran, Imran (Politeknik Kelautan dan Perikanan Karawang, BRSDM KP., 2025)
Fishermen at the Dufa-Dufa fish landing base, Ternate City, exploit yellowfin tuna using pole and line and FADs. Huhate is a fishing gear in the surface layer, so the yellowfin tuna that is caught is the yellowfin tuna that appears on the surface for the purpose of eating. In general, yellowfin tuna that gather on the surface of the water are classified as young fish. Therefore, yellowfin tuna caught around FADs tend to be young fish. This phenomenon causes the emergence of a problem, namely the dominance of young fish caught, besides that the yellowfin tuna fishery is an activity of exploiting fish resources with the aim of obtaining continuous profits. The aim of this research is to analyze biological aspects which include fork length structure and size of yellowfin tuna worth catching, analyze economic aspects which include profit analysis, net benefit cost ratio, internal rate of return, break even point, and payback period and analyze the status of the fishing business. sustainable yellowfin tuna. The research was carried out at the Dufa-Dufa fish landing base in Ternate City for 7 months, namely July 2022 - January 2023. The research method used was a survey method. The yellowfin tuna fishery business in the research location is dominated by the size not yet fit to catch, which is 100%. Financially and investment, the yellowfin tuna fishery business in the research location is feasible throughout the year. The yellowfin tuna fishery business based on the biological aspect has a low level of sustainability. Furthermore, based on the economic aspect (financial and investment criteria) the yellowfin tuna fishery business has high sustainability.